OLD GEORGIAN LITERATURE AS HISTORICAL SOURCE (VITAE, MARTYRDOMS), GEORGIAN CASE - Kadagishvili, Sopio (PEOPLE: International Journal of Social Sciences, 2020)
Critical approach of history actively started in Georgia from 19th century. This trend also effected on hagiographic monuments. Some scholars were mistrustful for adopting them as historical sources because of miracles and unnatural motives. That is why philologists were more interested in hagiographies than historians. At the same time historians were publishing, identifying texts and editions, revealing historical people, comparing hagiographic texts. Thus, enormous informational possibility became clear for many researchers. Today there is now doubt that hagiographic monuments (Vitae, Martyrdom) contain significant information while revealing cultural, social, political and economic factors of certain nations. Apart for solving many interesting issue from hagiographies, it is worth interesting to study Georgian hagiographies (with full of historism) in the context of history of mentality and identity. Years ago I was interested to study ethnic perception. Texts with various ethnic terms provoke me to observe (authentic) hagiographies. Certain conclusions were made through ethnic criteria based on theory of ethnicity. For instance, what was the content of ethnic terms: Relative and Nation? Changes the concept of that terms; How Georgian unity is concerned through centuries; Creating of national heroes in hagiographies and what historical process is related to this issue; What was self-perception and perception towards others. According hagiographic sources ∕ monuments such researches are not novelty not only for Georgian historiography, but foreign historiography as well. Alongside to political history that approach will make history more alive and comprehensive. For investigation I use ethnosymbolistic approach which ethnic markers represent important framework for the paper. According to the Georgian hagiographies of 10th-11th cc. we have deal with different perception of ethnicity towards Georgians, Armenians and Greeks.